Digital Health Interventions for Chronic Disease Management A Systematic Review - Yuli Sleven (Professorline, 2025)
Chronic diseases represent a significant global health burden, necessitating innovative approaches to enhance management and improve outcomes. Digital health interventions have emerged as promising tools to address the complex challenges of chronic disease management. This systematic review synthesizes current evidence on the effectiveness, implementation factors, and economic implications of digital health interventions across multiple chronic conditions. Implementation success was associated with user-centered design, simple interfaces, and healthcare provider involvement, while technical difficulties and limited digital literacy emerged as significant barriers. Economic analyses, available for 18 studies, indicated cost-effectiveness for interventions targeting respiratory conditions and diabetes. Digital health interventions offer effective approaches to enhance chronic disease management, with benefits spanning clinical outcomes, patient experience, and potentially healthcare resource utilization. Future research should prioritize longer-term evaluations, standardized outcome reporting, and studies in diverse populations to ensure equitable access and benefit. Successful implementation requires attention to design, integration with healthcare systems, and accessibility across diverse patient populations.